Cover Version and Copyright: Based on Copyright (Amendment) Bill 2014 of Hong Kong - Jing Bei (International Telecommunications Society (ITS), 2017)
Huge controversy has arisen since the Copyright (Amendment) Bill 2014 of Hong Kong, dubbed “Internet Article 23” by netizens, appeared in public view again, which was not adopted in the end. One of the concerns commonly raised by end users was whether uploading cover version (which refers to “online posting of earnest performance of copyright works” according to the Government's definition) would attract legal liability under the Bill. This article intends to first give an overview of the legal framework concerning cover version issue under Hong Kong copyright law. It then considers why such issue has provoked intense discussion in a political context. The article argues in conclusion that both the Government and public institutions can further their role in supporting creative and social innovation in music industry in the digital environment.
Keywords: 330; Copyright (Amendment) Bill 2014; earnest performance; cover version; copyright; legislation